2018
DOI: 10.1089/omi.2018.0160
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Human Anterior Pituitary Gland

Abstract: The pituitary function is regulated by a complex system involving the hypothalamus and biological networks within the pituitary. Although the hormones secreted from the pituitary have been well studied, comprehensive analyses of the pituitary proteome are limited. Pituitary proteomics is a field of postgenomic research that is crucial to understand human health and pituitary diseases. In this context, we report here a systematic proteomic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…Furthermore, a total of 6076 proteins identified from human NFPA tissues with TMT-based quantitative proteomics in this study (Supplemental Table 1) were compared to a total of 2175 proteins identified from human anterior pituitary gland with SDS-PAGE-LC-MS/MS and LC-LC-MS/MS ( Supplemental Table 12) (69). A total of 1933 proteins were identified in both NFPAs and anterior pituitary gland, 242 proteins were only identified in anterior pituitary gland but not in NFPAs, 4143 proteins were only identified in NFPAs but not in anterior pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a total of 6076 proteins identified from human NFPA tissues with TMT-based quantitative proteomics in this study (Supplemental Table 1) were compared to a total of 2175 proteins identified from human anterior pituitary gland with SDS-PAGE-LC-MS/MS and LC-LC-MS/MS ( Supplemental Table 12) (69). A total of 1933 proteins were identified in both NFPAs and anterior pituitary gland, 242 proteins were only identified in anterior pituitary gland but not in NFPAs, 4143 proteins were only identified in NFPAs but not in anterior pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution Fourier transform mass spectrometry is another promising novel technique which has identified 105 novel proteins in the normal anterior pituitary compared with previous high-throughput proteomic-based studies ( 327 ). Using this approach may also identify new candidate proteins and/or pathways driving pituitary tumorigenesis.…”
Section: Epigenetic Mechanisms Of Tumorigenesismentioning
confidence: 99%
“…Region‐specific data of the human anterior pituitary would more accurately clarify any alterations of secreted proteins, and would facilitate investigations on their physiological role. A systematic proteomic profile of human anterior pituitary glands identified 480 proteins with secretory potential and 187 N‐terminally acetylated proteins with high‐resolution Fourier transform MS (Yelamanchi et al, 2018). Accurate clarification of the role of the human anterior pituitary gland would accelerate precision medicine and biomedical research.…”
Section: Current Status Of Multiomics Studies Of Pasmentioning
confidence: 99%